Anticancer Effect of the Ethyl Acetate Fraction from Orostachys japonicus on MDA-MB-231 Human Breast Cancer Cells through Extensive Induction of Apoptosis, Cell Cycle Arrest, and Antimetastasis. (6th November 2019) - Kwon, Ji-Hye; Kim, Jae-Hyeon; Ryu, Deok-Seon; Lee, Hyun-Ji; Lee, Dong-Seok
Abstract : The antibreast cancer activities of the ethyl acetate fraction from Orostachys japonicus (OJEF) were investigated in MDA-MB-231 human breast cancer cells through WST assay, DAPI staining, flow cytometry analysis, and western blotting. OJEF effectively inhibited MDA-MB-231 cells by inducing apoptosis via intrinsic, extrinsic, and endoplasmic reticulum (ER) stress response pathways, cell cycle arrest at the G1/S phase, and antimetastasis including inhibition of tight junction, adherens junction, invasion, and migration. The MAPK family-mediated upstream signal transduction through p-p38 and p-ERK was considered to affect the downstream signal transduction including induction of apoptosis, cell cycle arrest, and antimetastasis. In conclusion, we executed an integrated study on the anticancer activities of OJEF, which extensively induced apoptosis, cell cycle arrest, and antimetastasis in estrogen-independent MDA-MB-231 human breast cancer cells known to be liable to metastasize.